Broad band anti-reflection 2-16μm coatings on diamond and ZnSe. - Hakim Khalili, Mohammad (Cranfield University, 2018)
In this project, Thin Metal Films an optical coating company is requiring the upgrade of a desktop research type radio frequency magnetron sputtering machine which was custom made for a European funded project and was gifted to it after the project completion. As the machine had no usage history, it had to be investigated and its capabilities and characteristics identified. The first part of the project, focused on restoring the machine using a systematic approach by utilising a technique called Plan Do Check Act, where a continuous feedback loop is used to identify problems and finding solution to them. Within the restoration process the aim was to improve the coating uniformity and machine’s repeatability. The restoration of the machine consumed almost the entire project duration leaving a little time for second part of the project. The second part was to use the restored machine, to develop single and multilayer Broad Band Anti-Reflective Coatings for Zinc Selenide and diamond optics. The optics are to be used in Attenuated Total Reflectance accessory units for Infrared spectroscopy. Based on the literature review and multiple decision criteria, yttria and ytterbia were showing promising results in adhering very well to a diamond surface and improving its transmission. Therefore, using Macleod software, a single layer quarter wavelength coating was designed and theoretically examined. It was found that a quarter wavelength ytteria at 5000 nm and a quarter wavelength ytterbia at 3370 nm can increase the transmission on both ZnSe and diamond optics to maximum of 98% and 95% accordingly. The coatings have not actually been deposited on the optics due to both targets breaking before conducting the actual experiments.
Keywords: Anti-reflective coatings; diamond prism; zinc selenide optics; yttrium; ytterbia; infrared; RF PVD sputtering; thickness uniformity